Varieties of Idealization and Strategies of Modification of Social Theory. The Case of the Totalitarian Syndrome - Brzechczyn, Krzysztof (Wydawnicwo Naukowe UAM, 2012)
The aim of this paper is to consider the influence of the methodological status of the concept of the totalitarian syndrome on the strategy of its development. It is argued that the totalitarian syndrome as put forward by Carl J. Friedrich and Zbigniew Brzezinski represented a kind of social modelling. However, there are different approaches to modelling in the social sciences. Modelling, when perceived from a neo-Hegelian perspectives, leads to the elaboration of dependencies between social phenomenon and their main factors. Modelling, when seen from a neo-Weberian perspective, relies on the construction of notions which systematize and order social phenomena. This hypothesis is illustrated by a methodological analysis of the extension of the totalitarian syndrome authored by Achim Siegel and Mark Thompson.
Keywords: idealization; totalitarianism; communism; methodology of social sciences; modeling; ideal types